Life Cycle of a Guinea Pig - Royston, Angela (Chicago, Illinois Heinemann Library, 1998)
An introduction to the life cycle of a guinea pig from the time a tiny pup is born until, eight months later, it is fully grown and ready to start a family of its own.
Keywords: Guinea pigs